(untitled) (Agroindustria, Sociedad y Ambiente, 2022)
The application of magnetic treatment to fuels is one of the most widely used alternatives today with the aim of reducing polluting gas emissions and increasing fuel savings. In this work, the effect of the magnetic treatment of fuel oil used in a steam production boiler was evaluated. Devices with an average magnetic induction of 0.36 T were used. With the introduction of magnetic technology in a boiler for the treatment of fuel oil, CO2 emissions were reduced by approximately 10.18 %, which contributes to reducing the contaminant load of these equipments. The CO emissions of this equipment decreased by approximately 60.07 %, so a more complete combustion is obtained. The magnetic treatment used caused a decrease of 13.84 % in the temperature of the exhaust gases, so the latent heat losses in the exhaust gases are reduced. Under the experimental conditions, the magnetic technology allows to increase the efficiency of the combustion process by 1.6 %, which could mean a greater use of energy in the system and potential fuel savings.